Probiotics for the treatment of antibiotic-associated diarrhea in children - N.Yu. Zavhorodnia; L.L. Petrenko (Zaslavsky O.Yu., 2019)
Antibiotic-associated diarrhea (AAD) is considered to be one of the most common complications of antibiotic therapy at the outpatient and inpatient stages of treatment in children. The major risk factors for the development of AAD are impaired colonization resistance of the intestinal microflora or direct mucosal irritation with the antibiotics (AB). Severe forms of AAD, known as pseudomembranous colitis, have been associated with Clostridium difficile infection (CDI), which is one of the leading causes in the structure of nosocomial and community-acquired infections and is characterized by considerable resistance to drug treatment. Alternative treatment strategies have been investigated, namely the possibility of adjuvant probiotic therapy, which may contribute to the normalization of indigenous microbiota impaired by AB and be appropriate for the prevention of AAD and CDI development. A review of the literature on the evaluation of the clinical efficacy of the prevention and treatment of AAD and CDI by probiotic drugs and certain probiotic strains was conducted. The literature was searched using electronic databases (Scopus, Web of Science, MedLine, The Cochrane Library, EMBASE, Global Health, CyberLeninka, RINC). The general characteristics of probiotic preparations are presented, the mechanisms of probiotic action are considered, and the bases of the effects of probiotic strains are analyzed. Data from randomized controlled trials have been systematized and analyzed; evidence of the effectiveness of AAD and CDI prevention and treatment by using probiotics is presented. The specific effects of probiotics on the prevention and treatment of AAD and CDI in children have been analyzed. The individual properties of the probiotic strain Lactobacillus rhamnosus GG are considered. The comparative characteristics of the evidence base of using probiotics in certain clinical situations are presented. Recommendations have been given to evaluate the possibility of using probiotic strains and to select a specific probiotic strain for the prevention and treatment of AAD and CDI in children receiving antibiotics.